ISC2 Certified Secure Software Lifecycle Professional (CSSLP) (2023) Cert Prep. - Brennen, Jerod (linkedin.com, 2024)
Prepare for the ISC2 Certified Secure Software Lifecycle Professional (CSSLP) certification exam.